Sympathy for the Devil: An Exploration of Federal Judicial Discretion in the Processing of White-Collar Offenders - Maddan, Sean (American journal of criminal justice, 2012)
Since the late 1990s, the United States has experienced a series of major corporate malfeasance events leading to the collapse of corporations such as Worldcom and Enron, predatory lending practices which devastated the nation’s real estate market and the Bernie Madoff scandal serving as prime examples. While the leading culprits in such well-publicized cases have met stiff sanctions, the common notion is that white-collar offenders are treated more leniently than street offenders by the criminal justice system. Given the scope and severity of victimization attributable to the contemporary white collar crime epidemic, the matter of sanctioning fairness and severity is of timely importance. This paper examines judicial discretion in the form of the decision to incarcerate and the length of sentences imposed for federal white collar and street level offenders. Findings inform discussion oriented around the related issues of deterrence and public safety.